Adjuvant radiation for T1-2N1 oral cavity cancer survival outcomes and utilization treatment trends: Analysis of the SEER database. (October 2018) - Torrecillas, Vanessa; Shepherd, Hailey M.; Francis, Sam; Buchmann, Luke O.; Monroe, Marcus M.; Lloyd, Shane; Cannon, Donald; Hitchcock, Ying J.; Weis, John R.; Hunt, Jason P.; Houlton, Jeffrey J.; Cannon, Richard B.
Highlights: 746 patients in the SEER database with T1-2N1 oral cavity cancer were analyzed. Adjuvant RT was associated with improved overall survival in T1-2N1 oral cavity cancer. Adjuvant RT was associated with improved disease-specific survival in T1-2N1 tumors. T1N1 tumors were less likely to receive adjuvant radiation. Utilization of adjuvant radiation for T1N1 tumors has decreased. Adjuvant RT should be strongly considered for all T1-2N1 oral cavity cancers. Abstract: Objective: Evaluate current practice patterns in the use of adjuvant radiation for T1-2N1 OCSCC patients and investigate its efficacy in the population-based setting. Materials and methods: This study extracted patients who were treated surgically for T1N1 and T2N1 OCSCC without adverse nodal features from the SEER database from 2004 to 2013. Patients with distant metastatic disease, unknown surgery or radiation status, or prior malignancies were excluded. Patients were divided into those who underwent surgical resection with and without adjuvant radiation. Disease-specific survival (DSS) and overall survival (OS) were the primary outcomes measured. Results: 746 patients met inclusion criteria and 70% received adjuvant radiation therapy. Treatment with adjuvant radiation therapy was significantly associated with improved 5-year DSS (65% versus 51%; p < 0.001) and OS (54% versus 44%; p = 0.007) for T1N1 tumors. Likewise, improved 5-year DSS (58% versus 38%; p = 0.009) and OS (48% versus 28%; p = 0.004) was shown in T2N1 tumors. Patients with T2N1 tumors wer significantly more likely to receive adjuvant radiation (75% versus 63%; p < 0.001). Those with insurance and high risk primary subsites: buccal, retromolar trigone, and hard palate were more likely to receive adjuvant radiation. The percent utilization of adjuvant radiation remained constant through the study period for T2N1 tumors (72–74%) but significantly decreased for T1N1 (71–55%) (p = 0.047). Conclusion: Adjuvant radiation therapy is independently associated with a significant survival benefit for patients with both T1N1 and T2N1 OCSCC. However, this study demonstrates that patients with T1N1 cancer are less likely to receive adjuvant radiation and utilization is decreasing.